2020
DOI: 10.1002/nau.24531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of bladder and bowel disorders in women with breast cancer: A systematic review with meta‐analysis

Abstract: Background: One of the consequences of breast cancer treatments may be the onset of new, or aggravation of preexisting bladder and bowel disorders. However, the presence and impact of these disorders in women with breast cancer are poorly documented. The aim of this systematic review was to assess the prevalence, incidence and impact of bladder and bowel disorders in women undergoing breast cancer treatment. Methods: A systematic search of six databases was conducted. Pooled prevalence rates and impact of blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Pelvic floor muscle training (PFMT) is the recommended first-line management of urinary incontinence (UI) [ 1 ]. Despite the high prevalence of UI (38%), specifically stress UI (37%), in women with breast cancer compared to women without breast cancer (21%) [ 2 ], PFMT to treat UI does not appear in breast cancer care pathways [ 3 ]. The potential link between breast cancer and UI is presumed to be a result of ovarian suppression secondary to the use of endocrine therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic floor muscle training (PFMT) is the recommended first-line management of urinary incontinence (UI) [ 1 ]. Despite the high prevalence of UI (38%), specifically stress UI (37%), in women with breast cancer compared to women without breast cancer (21%) [ 2 ], PFMT to treat UI does not appear in breast cancer care pathways [ 3 ]. The potential link between breast cancer and UI is presumed to be a result of ovarian suppression secondary to the use of endocrine therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing incidence of breast cancer, mortality rates are decreasing due to advancements in breast cancer treatments [ 2 ]. Recent literature reported that women with breast cancer may experience pelvic floor (PF) dysfunction including urinary incontinence (UI), faecal incontinence (FI) and sexual dysfunction after receiving treatment for breast cancer [ 3 , 4 ]. The development of these symptoms in women with breast cancer may be related to oestrogen depletion due to ovarian suppression and failure after chemotherapy or endocrine therapy use [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from quantitative studies have shown that women with breast cancer may experience a higher impact of PF dysfunction than women without breast cancer [ 3 , 12 ]. Recent data also indicate that the impact of PF dysfunction increases as women move on from their breast cancer diagnosis and enter the survivorship phase of their recovery (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…T, N, and M were used to determine the stage number, the size of the cancer tumor, and whether it has spread to surrounding tissue (T), lymph nodes (N), or progressed beyond the breast to other regions of the body (M). Apart from these, there are five stages of breast cancer, which are numbered as 0, 1, 2, 3, and 4 [ 9 , 10 ] and arementioned in Table 1 .…”
Section: Introductionmentioning
confidence: 99%